Key elements of virtually in higher education (Revista Electrónica Calidad en la Educación Superior, 2020)
As it comes to the use of ICT in education, teaching strategies are commonly established, but it is not considered as a tool for teaching mediation. In addition, this is what comes to be part of the fifth generation of distance education: virtual education. Therefore, understanding the different elements that lead to their development is important when subjects or curricula are implemented in virtual mode.
Keywords: Virtually; LMS; Instructional design; Curriculum